2017
DOI: 10.1111/tpj.13741
|View full text |Cite
|
Sign up to set email alerts
|

Root transcriptional dynamics induced by beneficial rhizobacteria and microbial immune elicitors reveal signatures of adaptation to mutualists

Abstract: SummaryBelow ground, microbe‐associated molecular patterns (MAMPs) of root‐associated microbiota can trigger costly defenses at the expense of plant growth. However, beneficial rhizobacteria, such as Pseudomonas simiae WCS417, promote plant growth and induce systemic resistance without being warded off by local root immune responses. To investigate early root responses that facilitate WCS417 to exert its plant‐beneficial functions, we performed time series RNA‐Seq of Arabidopsis roots in response to live WCS4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
167
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(196 citation statements)
references
References 62 publications
(115 reference statements)
9
167
0
6
Order By: Relevance
“…b), in later interaction stages of the interaction, when Rhizophagus colonized the roots, the AM fungus activates plant defenses, implying that it is ultimately recognized as an unwanted invader. Activation of root defenses can lead to growth–defense tradeoffs, resulting in inhibition of growth (Gomez‐Gomez et al ., ; Stringlis et al ., ), which could, at least in part, explain the growth reduction observed in Arabidopsis plants after colonization of the roots by Rhizophagus .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…b), in later interaction stages of the interaction, when Rhizophagus colonized the roots, the AM fungus activates plant defenses, implying that it is ultimately recognized as an unwanted invader. Activation of root defenses can lead to growth–defense tradeoffs, resulting in inhibition of growth (Gomez‐Gomez et al ., ; Stringlis et al ., ), which could, at least in part, explain the growth reduction observed in Arabidopsis plants after colonization of the roots by Rhizophagus .…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA was extracted from A. thaliana Col‐0 and M. truncatula A17 roots as previously described (Stringlis et al ., ). RNA‐seq library preparation and sequencing were performed by KeyGene (Wageningen, the Netherlands).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…These results suggest that rhizobia have active mechanisms to suppress PTI. Consistent with this, it has recently been shown that the plant‐growth promoting rhizobacterium Pseudomonas simiae WCS417 actively suppresses many transcriptional changes induced by the PAMP flg22 (Stringlis et al ., ). Plant pathogenic bacteria can suppress host immunity by secretion of effectors, many of which interfere with the canonical PTI pathway at different stages (Pfeilmeier et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Important influences on root development may come from abiotic stressors such as drought, salinity, and extreme temperature [13,14] not to mention biotic stressors such as pathogens [15][16][17][18]. One important biotic stressor-or helper-of particular recent interest is the rhizosphere and root-rhizosphere interactions [19][20][21]. The study of such interactions is enabled by non-destructive phenotyping technologies that can examine the phenotypic impacts of such interactions in soil during the stages of growth [22].…”
Section: Introductionmentioning
confidence: 99%